(untitled) (African Journal of Biomedical Research, 2024)
The fungal profile and pathogenicity indices associated with cucumber fruits were determined using standard microbiological methods. A total of one hundred and twenty-five (125) samples were randomly picked from five (5) different markets/ hawking points, transported in ice bags to Laboratory for analysis, prepared and made ready for microbiological analysis. Also pathogenicity tests were conducted on the identified isolates to establish both severity and percent disease index in the Koch postulates of disease development. The mean fungal count ranged from 1.0 x 103 ±0.25/±0.32 to 5.4 x 103 ±0.12. Isolates were characterized colonially, microscopically, and morphologically with their identities confirmed with reference chart. The four (4) isolates include Aspergillus species, Penicillium species, Fusarium species, and Cladosporium species. Due to high microbial thresholds of associated genus, there is need for all round awareness to avoid health outbreaks and pathogenesis tendencies, as some isolated species could produce potent toxins that are linked with food-borne illnesses. Bruises, pierces and surface wounds should be avoided at all times, having known the PDI of some isolates. Infestation by rodents and insects during storage should be avoided as it may constitute serious health and deterioration exposures. Washing of fruits with salted-water before eating is most recommended, as transit eating of any kind should be discouraged.